2010
DOI: 10.2169/internalmedicine.49.2618
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Risk of Intercostal Artery Laceration During Thoracentesis in Elderly Patients by Using 3D-CT Angiography

Abstract: Objective Our study was undertaken to determine the location of the tortuous intercostal artery in elderly patients by using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 3 publications
0
24
0
4
Order By: Relevance
“…This tendency decreases with increasing distance from the spinal column, and the artery is usually protected, even in older individuals, at the point where the ribs angle forward. 11 Our practice is to perform all chest tube insertions (and thoracenteses) laterally at or anterior to the posterior axillary line, unless loculations necessitate a posterior approach. Ultrasound guidance is essential for this approach and is a second factor that we believe would decrease the incidence of complications due to chest tube insertion.…”
Section: Discussionmentioning
confidence: 99%
“…This tendency decreases with increasing distance from the spinal column, and the artery is usually protected, even in older individuals, at the point where the ribs angle forward. 11 Our practice is to perform all chest tube insertions (and thoracenteses) laterally at or anterior to the posterior axillary line, unless loculations necessitate a posterior approach. Ultrasound guidance is essential for this approach and is a second factor that we believe would decrease the incidence of complications due to chest tube insertion.…”
Section: Discussionmentioning
confidence: 99%
“…92 The ICA is more exposed in the intercostal space within the first 6 cm lateral to the spinous processes and can be seen as far lateral as the midaxillary line. [92][93][94][95] Thus, the ICA will most likely be avoided if a procedure site is selected >6 cm lateral to the spinous processes and the needle is inserted above the rib. Second, although all three studies conducted using real-time (dynamic) ultrasound guidance reported a pneumothorax rate of <1%, it is uncertain whether real-time ultrasound guidance confers any additional benefit compared to static guidance for site marking as direct comparisons were not made.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…However, the ICA can have a tortuous and unpredictable course. [45][46][47][48][49] In a CT scan study of 81 patients, Choi et al demonstrated increased tortuosity in elderly patients which decreased the effective ''safe'' space for puncture. 47 Yoneyama and colleagues also performed a CT angiography study in elderly patients and found that the lateral side (9-10 cm from spine) had a larger percentage area of safety than the medial side (5-6 cm from spine; 79.8% vs 61.2%; P < .0001).…”
Section: Anatomy Of Thoracentesis: Aiming For the ''Triangle Of Safety''mentioning
confidence: 99%